A highly photoresponsive and efficient molybdenum‑modified titanium dioxide photocatalyst for the degradation of methyl orange - Kanakaraju, Devagi; Muhamad Akif Aizuddin, Bin Jasni; Y. C., Lim (Springer, 2021)
The degradation of azo dyes in aquatic environments is still challenging due to their stability and perpetual effect. This work demonstrates the application of highly ultraviolet-responsive titanium dioxide/molybdenum photocatalyst to degrade methyl orange. A series of titanium dioxide/molybdenum photocatalyst with different molybdenum concentrations (1–10 wt%) were synthesized by a facile wet impregnation method. The introduction of molybdenum has favorably induced changes in surface morphology, crystallite size, optical absorption, and specific surface area, which have collectively enhanced the photocatalytic performance of titanium dioxide/molybdenum photocatalyst on the removal of methyl orange. A systematic investigation on the influencing parameters such as photocatalyst dosage, initial methyl orange concentration, and initial pH was investigated, and the optimum conditions were achieved. The best-performing titanium dioxide/molybdenum (3 wt%) photocatalyst yielded a 94.5% methyl orange photodegradation efficiency within 120 min of irradiation. The dopant concentration, photocatalyst dosage, and pH were investigated to validate the optimized conditions for titanium dioxide/molybdenum on methyl orange removal using response surface methodology via the Box–Behnken design. The present results demonstrated that both the superoxide radical and hydroxyl radical play a primary role in the degradation mechanism. This study provides fresh insight that the successful structural modification of titanium dioxide by molybdenum could enhance the photocatalytic removal of dye wastewater.